(untitled) (Kriminalističke teme, 2007)
The right on privacy is one of the basic rights which is defined in Convention for the Protection of Human Rights and Fundamental Freedoms and Convention for the Protection of individual with Regard to Automatic Processing of Personal Data, and in some documents which are specific for police, such as European Code of Police Ethics and Declaration on the Police. Standards which are defined in these documents are analyzed in this text. Very significant for police practice are explanations of European Court for Human Rights, which in its decisions, gives us very useful opinions and interpretations, which also will be analyzed in this paper. Another thing which is particularly important for police work and practice are these Court references to instrument of legal protection in our national law. Therefore, in the second part of this article national legal base is analyzed, especially our Police Law Act, our criminal proceedings law acts, in order to see the level of harmonization between our law and international standards in protection of this right. At the end of this article there is a reference to work of private security organization and potential state responsibility for absence of legal base for their work, in order to protect right on privacy.